Economic Growth with Two Endogenous Factors - Niehans, Jurg (Quarterly Journal of Economics, 1963)
Introduction, 349. — I. The two class model, 351. — II. The one class model: diminishing returns, 358. — III. The one class model: infinite growth with constant returns, 365. — Concluding remarks, 370